SOSIALISASI DESA SADAR LINGKUNGAN DAN PEMILAHAN SAMPAH - Hidayat, Raden Aldi; Iskandar, Aulia Pratiwi; Sopiyani, Nuzula; Alfan, Muhammad; Farhan; Qalbiah, Nurul; Sulastri, Sri; Fanesa, Mawar; Ruliansyah, Muhammad (Jurnal Wicara, 2024)
This socialization explains how public awareness is about waste in the surrounding environment and how to sort waste. KKN students provide facilities for the Teniga Village community regarding waste with the Environmental Service as the resource person with the aim of increasing public awareness regarding waste sorting which will later be sold to improve the community's economy. Students conducted a location survey to find out the waste problem in Teniga Village.